HUBUNGAN SIKAP GOTONG ROYONG DENGAN MOTIVASI BELAJAR MATEMATIKA SISWA DI MA AL-MUSTAQIM - Hafizt, Ilham (UNIVERSITAS TANJUNGPURA, 2025)
Education plays a crucial role in the advancement of a nation, and learning motivation as well as the spirit of cooperation are key factors in the learning process. This study aims to investigate the relationship between the spirit of cooperation and mathematics learning motivation among students at MA Al-Mustaqim. The research employs a quantitative approach using a correlational method, involving 25 students, with 9 students from class XI and 16 students from class XII IPA as the sample. Data were collected through closed-ended questionnaires measuring the spirit of cooperation and learning motivation using a Likert scale. The analysis results indicate that the spirit of cooperation data do not follow a normal distribution, while the learning motivation data do. Statistical testing using Spearman Rank correlation yielded a significance value of 0.006, indicating a significant relationship between the spirit of cooperation and mathematics learning motivation, with a correlation coefficient of 0.536, categorized as strong. This research is expected to provide references for teachers in enhancing the quality of the teaching and learning process.